Elucidation of the relationships of structure-process-property for different ethylene/α-olefin copolymers during film blowing: An in-situ synchrotron radiation X-ray scattering study. (May 2020) - Zhao, Haoyuan; Zhang, Qianlei; Xia, Zhijie; Yang, Erjie; Zhang, Mengnan; Wang, Yusong; Ji, Youxin; Chen, Wei; Wang, Daoliang; Meng, Lingpu; Li, Liangbin
Abstract: The copolymerization of ethylene and different α-olefins could result in polyethylene (PE) with different structural topologies, and lead to polyethylene products with different macroscopic performances. Herein, three different polyethylene samples, namely low-density polyethylene ( l -PE), metallocene catalyzed ethylene-hexene copolymer ( h -PE) and ethylene-octene copolymer ( o -PE), were selected as representatives to construct the structure-process-property relationship during film blowing. The detailed crystal-based network evolution during film blowing was first characterized by in-situ synchrotron radiation X-ray scattering. The crystallization process of l -PE film is determined by the coupling effects of temperature and flow, while those of h -PE and o -PE films are dominated by the temperature. Furthermore, the hierarchical crystal structure from the molecular scale to micrometers of final films and segmental dynamics were systematically characterized by multiple ex-situ characterization techniques, i.e. Solid-State NMR, FTIR, SEM. l -PE film shows the crystalline morphology of the row-nucleated structure, whereas h -PE and o -PE show spherulite-like superstructure with better mechanical properties. The current study tentatively constructs the relation of primary chemical structure, microstructural evolution and macroscopic performances of different polyethylene copolymers during film blowing. Highlights: Three ethylene/α-olefin copolymers were selected to construct the structure-process-property relationship on the film blowing. The structural evolution during film blowing was captured by a combination of in-situ SR-SAXS/WAXS and a custom-built film blowing device. The multi-scale microstructure and dynamics of final films were characterized by ex-situ SAXS/WAXS, FTIR, SEM, and SS NMR. The mechanical and optical properties of films are well correlated with their structural evolution and microstructure.